ANALISIS TINGKAT PELAKSANAAN KREDIT MIKRO (DANA BERGULIR) DI PERGURUAN TINGGI Study Kasus pada Mahasiswa Diploma Tiga Bisnis Kewirausahaan Universitas Gunadarma Periode 2015 - 2016 - Laminiasih Lasminiasih (Faculty of Economics and Business, Universitas Malikussaleh, 2018)
This study aims to analyze the success rate of micro credit activities or revolving funds in universities. This research method uses descriptive qualitative analysis by explaining the procedure in running micro credit activity and analyzing student ability level in running micro credit activity. The data used are primary data and secondary data by conducting interviews and financial analysis. The result of this research is that students of Diploma Three Business and Entrepreneurship in conducting micro credit activities run in accordance with the procedure which has been determined, which can be seen from the result of profit rate from micro credit activity equal to 20% and micro credit refund rate of 21% and in this activity no symptoms of experiencing bad credit or students can not return the funds that have been given as venture capital. Thus the microcredit activities that run the students can run well in running the business.